Standardization of Trauma Symptoms Checklist for Children - Parvaneh Mohammadkhani; Mohammad Ali Nazari; Ebrahim Rezaee Dogaheh; Mohammad Raza Mohammadi; Hedieh Azadmehr (Psicologia, 2007)
The aim of this study was to standard and assign validity and reliability of the Trauma Symptom Checklist for Children – TSCC-A. Normative data for the TSCC-A were based on 3042 students participating in a prevalence child abuse study in 19 different locations of Tehran and 140 participants who had been referred to the run away children centers in Tehran. After the TSCC was validated on run away and abused children, it was made available to researchers doing larger studies on normative group. Reliability analysis of the TSCC-A scales in the normative sample demonstrated high internal consistency. The evidence for its validations (convergent, discriminate and construct validity) showed that they were significantly acceptable. This paper presents data demonstrating the psychometric reliability and validity of the TSCC-A scales in Iranian student population. We suggest to include the TSCC-A in a battery of relevant standardized tests.